Multivalent Batteries—Prospects for High Energy Density: Ca Batteries - Monti, Damien; Ponrouch, Alexandre; Araujo, Rafael B.; Barde, Fanny; Johansson, Patrik; Palacín, M. Rosa (Frontiers in Chemistry, 2019)
Batteries based on Ca have promise of leap-frog increase in energy densities and are especially attractive as Ca is the 5th most abundant element on Earth’s crust. The viability of Ca metal anodes has recently been shown by approaches of either wide potential window electrolytes at moderate temperatures or THF based electrolytes at room temperature. This paper provides realistic estimates of the practical energy densities for Ca metal anode based rechargeable batteries at the cell level, calculated using open source models for several positive electrodes and electrolytes. The results indicate that doubled or even tripled energy density as compared to the state-of-the-art LIB is viable – if a practical proof-of-concept can be achieved.